2020
DOI: 10.1002/da.23123
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a machine learning‐based postpartum depression prediction model: A nationwide cohort study

Abstract: Background Currently, postpartum depression (PPD) screening is mainly based on self‐report symptom‐based assessment, with lack of an objective, integrative tool which identifies women at increased risk, before the emergent of PPD. We developed and validated a machine learning‐based PPD prediction model utilizing electronic health record (EHR) data, and identified novel PPD predictors. Methods A nationwide longitudinal cohort that included 214,359 births between January 2008 and December 2015, divided into mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 37 publications
(50 reference statements)
4
43
2
Order By: Relevance
“…It should be noted that these associations do not imply casual effects between the predictor variables and the outcome. Our results are consistent with a recent study [17] that reported an AUC of 0.71 for an EHR-based PPD prediction model applied to an Israeli cohort of 214K women with PPD prevalence of 1.9%. Our cohort had significantly higher prevalence of PPD (13.4%) and included only first live births.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It should be noted that these associations do not imply casual effects between the predictor variables and the outcome. Our results are consistent with a recent study [17] that reported an AUC of 0.71 for an EHR-based PPD prediction model applied to an Israeli cohort of 214K women with PPD prevalence of 1.9%. Our cohort had significantly higher prevalence of PPD (13.4%) and included only first live births.…”
Section: Discussionsupporting
confidence: 93%
“…This limits the availability of reliable outcome measures and may introduce biases. Recently, a PPD prediction model using primary care EHR was reported to achieve AUC of 0.71 on a nationwide cohort [17]. The rate of PPD in this cohort was 1.9%, which is lower than the estimated population level prevalence.…”
Section: Introductionmentioning
confidence: 69%
“…Indeed, prenatal screening for anxiety can be implemented into prediction models used to earlier identify mothers and offspring at risk. [50]…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Secondly, there is subjective deviation in the diagnosis of depression in clinic [ 5 ]. At present, the common method of the diagnosis of depression is mainly based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), which is subjective by doctors’ interviews with patients and evaluation scales [ 6 , 7 ]. Thus, it is difficult to identify depression, and there are some missed diagnoses and misdiagnoses.…”
Section: Introductionmentioning
confidence: 99%